SAT0142 Immunogenicity Assessment of PF-06438179, A Potential Biosimilar to Infliximab, In Healthy Volunteers. (9th June 2015) - Udata, C.; Yin, D.; Cai, C.-H.; Hua, S.Y.; Salts, S.; Rehman, M.I.; AL-Sabbagh, A.; McClellan, J.; Meng, X.
Abstract : Background: PF-06438179 is being developed as a potential biosimilar to Remicade® (infliximab) in a stepwise approach following globally accepted regulatory guidelines. PF-06438179 was shown to have an identical primary amino acid sequence and similar physicochemical, in vitro and in vivo functional properties to infliximab reference products sourced from the European Union (infliximab-EU) and United States (infliximab-US). Objectives: PF-06438179 was evaluated for immunogenicity in a Phase I pharmacokinetic (PK) similarity study; safety was also evaluated. Methods: In this double-blind trial (NCT01844804 ), 146 healthy volunteers received a single 10-mg/kg IV dose of PF-06438179 (n=49), infliximab-EU (n=48) or infliximab-US (n=49). All subjects provided informed consent. Safety and immunogenicity were evaluated over 12 weeks and PK over 8 weeks. Serum samples for detecting anti-drug antibodies (ADA) and neutralizing antibodies (NAb) were collected up to 12 weeks postdose. ADA samples were analyzed using 2 validated electrochemiluminescent immunoassays, 1 each to detect ADA against PF-06438179 and reference drugs (infliximab-EU or -US). A tiered approach of screening, confirmation and titer quantitation was used. Samples were tested first for ADA against the dosed product and confirmed ADA-positive samples were tested for ADA cross-reactivity using the alternate ADA assay. ADA-positive samples were analyzed for NAb using a validated semi-quantitative cell-based assay against the dosed product and for NAb cross-reactivity using the alternative NAb assay. Cross-reactivity was also examined using the alternate ADA assay for the week 12 samples that tested negative against the dosed product. Results: Samples for immunogenicity assessment were collected from 146 subjects. No subject tested positive for ADA at baseline. Six out of 37 (16.2%), 14/43 (32.6%) and 11/39 (28.2%) subjects in the PF-06438179, infliximab-EU and infliximab-US groups, respectively, had ≥1 ADA-positive sample through Day 85. Of these 31 subjects, 27 (6/6 PF-06438179; 10/14 infliximab-EU; 11/11 infliximab-US) also tested positive for cross-reactivity by alternative assay, suggesting that ADA were likely developed against epitopes shared among study drugs. Of the 31 subjects who tested ADA positive, 26 tested positive for NAb (5/6 PF-06438179; 12/14 infliximab-EU; 9/11 infliximab-US). Cross-reactivity was further demonstrated by negative ADA samples, which were confirmed by alternative assay. Overall safety profiles were similar across the three cohorts and no infusion related reactions were reported. Conclusions: The three study drugs had comparable immunogenicity profiles, however, a lower incidence of ADA response was observed in the PF-06438179 group. The majority of ADA-positive subjects also developed NAb. PF-06438179 demonstrated PK similarity and comparable safety profiles to infliximab-EU and -US in healthy subjects. An ongoing global, comparative study assessing the efficacy and safety of PF-06438179 and infliximab-EU in subjects with active rheumatoid arthritis who had an inadequate response to methotrexate will include a comparative assessment of immunogenicity. Disclosure of Interest: C. Udata Employee of: Pfizer Inc, D. Yin Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, C.-H. Cai Employee of: Pfizer Inc, S. Hua Employee of: Pfizer Inc, S. Salts Employee of: Pfizer Inc, M. Rehman Employee of: Pfizer Inc, A. AL-Sabbagh Employee of: Pfizer Inc, J. McClellan Employee of: Pfizer Inc, X. Meng Employee of: Pfizer Inc